Impact of Forest Stewardship Council on Integrated Pest Management in Certified Plantations of South Africa - Lemes, Pedro G.; Lawson, Simon A.; Zanuncio, José C.; Jacovine, Laercio A.G.; Torres, Carlos M.M.E.; Wilcken, Carlos F. [UNESP] (Emerald, 2022)
“Highly hazardous” pesticides have been listed and banned in Forest Stewardship Council (FSC) certified areas and producers from tropical countries in the southern hemisphere, such as Australia, Brazil and South Africa suffer the consequences of these restrictions. The objective was to assess changes and costs of FSC forest certification in the pest management from the perspective of certified foresters in South Africa. Questionnaires were sent to for all FSC certified forest plantations managers in South Africa until July 2014. Deltamethrin was considered the most needed active ingredient in derogation, but cypermethrin and alpha-cypermethrin were also considered necessary. A total of 37.5% of respondents were totally dissatisfied with the cost/benefit ratio of FSC certification related to pest management. Excessive rigidity and a lack of justifiable criteria for banning chemicals may turn the certification process difficult and reduce its adoption in South Africa, although FSC certification has made pest management more sustainable.
Keywords: Certification; Forest entomology; IPM; Pesticides; Sustainable forest management